Fat splitting the manufacture of fatty acids from coconut oil - Arzadon, Purita; Gutierrez, Linda; Supleo, Elvira (Quezon City College of Engineering, 1964)
From the computations involved in this design, it is found out that the establishment of a fatty acid plant in the Philippines would be most profitable for both the establishment and the country. Profitable for the company because it makes as mush as P 1,000,000 profit before taxes annually for itself; profitable for the country because instead of importing chemicals from abroad, it can keep its reserves within the country. Besides it will not be spending as much as when it imports the chemicals from abroad. The calculated payoff time of four years and the reported concentration of greater that 90% will also be the advantage of the plant. In only a short time, the plant will be able to gain back all its original investment. Also, the greater the purity of the product, the better.
Typescript.
Plant design.
Keywords: Factories -- Design and construction; Fatty acids; Coconut oil